Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Biologi Kelas X Ipa SMA Negeri 1 Rengat - Athira Sapriani; Sepita Ferazona (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The research conducted in class X IPA SMA Negeri 1 Rengat aims to determine the level of student learning difficulties in biology subjects in class X IPA SMA Negeri 1 Rengat. This study used a cluster sampling sample with a population of 90 students of class X IPA. Data analysis in this study used percentage techniques. The results of the study showed that the level of learning difficulties of students at SMA Negeri 1 Rengat, physiological indicators were 56.4% in the sufficient category, psychological indicators were 65.26% in the sufficient category, family indicators were 66.01% in the sufficient category, school indicators were 59.46% in the sufficient category, community indicators were 62.5% in the sufficient category, the average overall percentage was 61.92% in the good enough category.